Melissus’ and Zeno’s Deductive Speech (Revista Archai, 2024)
This paper explores the prosaic deductive style developed by Melissus and Zeno. It first emphasizes the authors’ use of a systematic and reduced vocabulary solely dedicated to a priori deduction. In a second time, the paper delves into the systematic role of reductio ad absurdum in their reasoning and distinguishes several kinds of reductio employed by the authors. Through this analysis, the study shows how Melissus and Zeno not only developed and systematized certain aspects of Parmenides’ style but also introduced original features that significantly influenced the philosophical writing style.